Ethno- Religion Cum Geo-Political Background to the Russo-Ukraine War - Duyile William Abiodun (Lakhomi Journal Scientific Journal of Culture, 2023)
The paper examined and further investigated the historical, ethnical and religious links between Russia and Ukraine and the factors that led to the war. The paper relied on secondary sources. Secondary sources included literature such as books and newspapers. The documentary data were subjected to internal and external criticism for authentication and then to textual and contextual analysis The paper found out Ukraine policy direction and friendship with Europe and the United States of America.